TENDENCIES OF USING ADDITIONAL TEACHING AIDS DURING LESSONS IN GENERAL EDUCATION SCHOOLS OF LITHUANIA - Kalvaitis, Albinas (Acta Paedagogica Vilnensia, 2014)
In the present study, 6575 lesson observation protocols from 98 general education schools located in various Lithuanian municipalities, prepared by the National School Evaluation Agency exterior assessors, have been analysed. The lesson observations were organized when exterior auditors were making an audit in these schools. Lesson observation protocol analysis was made in 2011. Also, the teaching aids classificator, prepared by the author and used for the analysis, is included in the article. It has been estimated that approximately in two thirds of the observed lessons general education teachers use some additional teaching aids besides a coursebook. Additional teaching aids are especially often used during the Information Technology (IT) and music lessons (almost always), as well as in teaching geography and biology. Most rarely additional teaching aids are used during mathematics and the Lithuanian mother tongue lessons. Teachers mostly use traditional visual aids (posters, maps, models, etc.) audiovisual teaching aids oriented towards general work (slides, films, etc.) and handouts prepared by themselves. Teachers, even without knowing that an exterior auditor might come to the lesson, usually use the teaching aids that are oriented towards individual pupils’ work. The analysis has also shown that teachers of experimental sciences even in “demonstrational“ lessons allocate too little time to show practical processes and instead are oriented towards the whole class and not to idividual work and use audiovisual, visual digital teaching aids (mostly slides).
Keywords: teaching aid; general education schools; teacher; pupil; lesson